Scratch-resistant polarizing plate and method for manufacturing the same
Patent Information
- Application Number
- CN202611483442.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-22
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]针对现有技术存在的背光源侧丙烯酸树脂薄膜易划伤以及高固含量硬质涂层易团聚脱落的问题,本申请通过一种耐划伤偏光板及其制备方法,实现了在保证高透光率的同时显著提升偏光板背光源侧表面的耐划伤性能
[0019](1)通过重构层叠结构,将primer层置于丙烯酸树脂薄膜的最外侧,使其作为牺牲防护层直接承受背光模组的机械摩擦,从物理路径上隔绝了对软质丙烯酸树脂基体的直接损伤。
Smart Images

Figure CN123010153A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of optical thin film technology, specifically to a scratch-resistant polarizing plate and its preparation method. Background Technology
[0002] In LCD modules, polarizers typically use polyvinyl alcohol (PVA) polarizers as their core, with optical protective films laminated on both sides to provide mechanical support and environmental protection. With the trend towards thinner and lighter display devices, acrylic resin films such as polymethyl methacrylate (PMMA) are increasingly being used as protective films for the backlight side due to their high transmittance and low birefringence. However, acrylic resin films have relatively low surface hardness. During module assembly and transportation, their outer surfaces come into direct contact with the backlight module's light guide plate, reflector, or metal frame, making them prone to scratches from friction and pressure, leading to optical defects or even product failure.
[0003] To improve scratch resistance, existing technologies attempt to coat the protective film surface with a hard coating containing silica particles. However, in practical applications, simply increasing the solid content of silica particles to increase the density of surface hard bumps can easily lead to agglomeration due to the reduced interparticle spacing and enhanced surface hydroxyl effects. Agglomeration results in hard bumps of varying heights on the coating surface: excessively high bumps become stress concentration points, making the surrounding resin easily torn and peeled off during scratching; excessively low bumps lack effective support, leaving the resin body directly exposed and damaged. Furthermore, in traditional polarizer structures, the primer layer is typically located between the acrylic resin film and the adhesive layer (i.e., on the inner side), leaving the outer surface of the acrylic resin film directly exposed to the backlight module, failing to fundamentally solve the scratch problem on the outer surface. Summary of the Invention
[0004] To address the problems of easy scratching of acrylic resin films on the backlight side and easy agglomeration and peeling of high-solids-content hard coatings in existing technologies, this application proposes a scratch-resistant polarizing plate and its preparation method, which significantly improves the scratch resistance of the backlight side surface of the polarizing plate while ensuring high light transmittance.
[0005] To achieve the above objectives, this application adopts the following technical solution: This application provides a scratch-resistant polarizing plate, comprising, from top to bottom, a compensation film, a first adhesive layer, a polarizer, a second adhesive layer, an acrylic resin film, and a primer layer; wherein, the primer layer is disposed on the side of the acrylic resin film away from the polarizer; the primer layer includes a resin crosslinking network and silica particles anchored in the resin crosslinking network; the arithmetic mean roughness Ra of the primer layer surface is 0.01 μm to 0.12 μm; the solid content of the silica particles in the primer layer is 11% to 30%, and the solid content percentage is the percentage of the solid mass of the silica particles to the total solid mass of the primer layer.
[0006] In the above scheme, the primer layer is disposed on the outer side of the acrylic resin film (the side away from the polarizers), allowing the primer layer to directly contact the backlight module instead of the acrylic resin film, structurally avoiding direct wear of the soft resin matrix. Simultaneously, the solid content of silica particles is controlled within the range of 11% to 30%, and the arithmetic mean roughness Ra is adjusted to 0.01 μm to 0.12 μm, resulting in a highly uniform micro-nano uneven structure on the coating surface. When the solid content is below 11%, the particles are completely coated by the resin, and the surface lacks sufficient hard support points; when it is above 30%, severe particle stacking leads to uncontrolled Ra, and protruding particles are prone to detachment during friction. Within the scope defined in this application, silica particles, acting as hard micro-protrusions, bear the main frictional load. The highly uniform micro-protrusions can evenly distribute the scratching stress throughout the coating, avoiding resin tearing or particle peeling caused by localized stress concentration. Preferably, the solid content of the silica particles can be 13%, 15%, 18%, 20%, 23%, 25%, 27%, 29%, etc.
[0007] As a further improvement of this application, the thickness of the primer layer is 120 nm to 400 nm; the resin crosslinking network is formed by crosslinking waterborne polyurethane and a multifunctional oxazoline polymer, and the surface of the silica particles is grafted with active groups, which are connected to the resin crosslinking network through the active groups as crosslinking nodes; the secondary particle size of the silica particles is 30 nm to 250 nm. The secondary particle size of the silica particles refers to the particle size of silica in the silica sol.
[0008] In this embodiment, silica particles participate in the three-dimensional network formed by waterborne polyurethane and multifunctional oxazoline through surface-grafted active groups as chemical crosslinking nodes. This chemical anchoring mechanism prevents the migration and aggregation of particles during the coating and drying process, ensures the stability of particle dispersion under high solid content, makes the surface micro-protrusions highly uniform, and ensures the precise controllability of Ra value.
[0009] As a further improvement of this application, the surface of the silica particles is grafted with rigid groups that provide steric hindrance and carboxyl groups as the active groups; the hydroxyl groups on the surface of the silica particles are connected to silane coupling agent residues through Si-O-Si bonds, and the epoxy groups of the silane coupling agent residues react with the amino groups of 3,5-diaminobenzoic acid to form bonds, thereby introducing the rigid groups and the carboxyl groups, wherein the rigid groups are benzene ring-containing groups.
[0010] In this embodiment, the rigid benzene ring group introduced by 3,5-diaminobenzoic acid provides steric hindrance, suppressing the tendency of silica particles to agglomerate due to van der Waals forces and hydrogen bonding at high solid content. The introduced carboxyl group reacts chemically with the polyfunctional oxazoline during curing, firmly locking the particles in the resin network. This dual effect ensures that even at a high solid content of 11% to 30%, the particles remain monodisperse, avoiding surface defects and reduced scratch resistance caused by agglomeration.
[0011] As a further improvement of this application, the primer layer is formed by applying a primer coating solution and drying it. The preparation method of the primer coating solution includes: diluting the aqueous polyurethane emulsion with water, adding the silica particle sol and the multifunctional oxazoline polymer, stirring evenly, filtering, and allowing it to stand to remove bubbles, thereby obtaining the primer coating solution. This embodiment specifies a particular order of addition, diluting the aqueous polyurethane first and then adding the particle sol and crosslinking agent, which helps maintain the colloidal stability of the system, avoids flocculation caused by excessively high local concentrations, and ensures the uniformity and surface quality of the coating. To improve coating performance, the primer coating solution may further contain other additives such as defoamers, leveling agents, and antistatic agents.
[0012] As a further improvement of this application, the acrylic resin film is made from polymethyl methacrylate resin through melting, extrusion, and stretching; the film thickness of the acrylic resin film is 20μm to 80μm, and the total light transmittance is 92% to 98%.
[0013] As a further improvement of this application, the first adhesive layer and the second adhesive layer comprise an epoxy group resin prepolymer and a cationic photoinitiator; the thickness of the cured first adhesive layer and the second adhesive layer is both 1 μm to 5 μm. This embodiment uses a cationic curing system, which has the advantages of low shrinkage and strong adhesion compared to free radical curing. Furthermore, by controlling the adhesive layer thickness to a thin layer range of 1 μm to 5 μm, it ensures the bonding reliability between the functional layers while avoiding optical distortion or residual internal stress caused by excessively thick adhesive layers.
[0014] As a further improvement of this application, the compensation film refers to an optical film commonly used in the industry that has optical compensation or viewing angle compensation effects. For example, the compensation film can be an optical film with a wavelength of λ / 2, λ / 4, or λ / 8 wavelength, a full-wave plate, as well as a viewing angle compensation film, an O-TAC film, etc., or a phase difference film with positive wavelength dispersion, reverse wavelength dispersion, or flat wavelength dispersion. Considering the direction of the optical axis, the compensation film can be, for example, an A-plate with the optical axis parallel to the film surface, a C-plate with the optical axis perpendicular to the film surface, an O-plate with the optical axis inclined relative to the film surface, or a biaxial compensation film with biaxiality. The compensation film is a polymer film that has been given birefringence through stretching, casting, or extrusion; and a liquid crystal cured layer formed by orientation and curing of a liquid crystal compound. As a material of the polymer film, the compensation film includes at least one of cyclic olefin polymers, cellulose triacetate, polyester resins, polycarbonate resins, polyimide resins, acrylic resins, or polystyrene resins. Examples of cellulose-based resins include triacetylcellulose, diacetylcellulose, and mixtures or copolymers thereof, such as TAC materials with trade names PK3 and NR01, and O-TAC films with a phase difference of 0. Examples of polyester-based resins include polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, and copolymers or mixtures thereof. Examples of cyclic olefin-based resins include cyclic olefin polymers (COP) and cyclic olefin copolymers (COC), and COP material with the trade name Sanuqi. Examples of polyimide-based resins include aliphatic polyimides and aromatic polyimides. Examples of liquid crystal compounds include nematic liquid crystal polymers, disc-shaped liquid crystal polymers, reactive liquid crystal monomers, and mixtures thereof. These liquid crystal compounds can be oriented by rubbing, photo-orientation, or electric field orientation, and form a liquid crystal cured layer by thermosetting or photo-curing (e.g., UV curing). The optical compensation film can be a single-layer structure, a multi-layer structure including a substrate and a liquid crystal curing layer, or a multi-layer structure composed of multiple phase retardation films, such as B+C, A+C, etc. The thickness of the compensation film is 0.1μm to 200μm.
[0015] As a further improvement of this application, the polarizer is prepared from a polyvinyl alcohol film through a process of swelling, dyeing, stretching, washing and drying.
[0016] This application also provides a method for preparing a scratch-resistant polarizing plate as described in any of the above claims, comprising: providing an acrylic resin film with a primer layer on its surface; and attaching a compensation film and the acrylic resin film with the primer layer to both sides of a polarizer via a first adhesive layer and a second adhesive layer, wherein the primer layer faces away from the polarizer.
[0017] As a further improvement of this application, in the step of bonding the compensation film and the acrylic resin film with the primer layer to both sides of the polarizer, the first adhesive layer and the second adhesive layer are cured by ultraviolet irradiation.
[0018] The specific benefits of this application are as follows: The scratch-resistant polarizing plate and its preparation method provided in this application solve the problem of easy scratching of the protective film on the backlight side through the synergy of structural design and material modification.
[0019] (1) By reconstructing the stacked structure, the primer layer is placed on the outermost side of the acrylic resin film, so that it can directly bear the mechanical friction of the backlight module as a sacrificial protective layer, thus isolating the soft acrylic resin matrix from the physical path.
[0020] (2) A linkage control mechanism between solid content and surface roughness was established. With a solid content of 11% to 30% silica and an arithmetic mean roughness Ra of 0.01 μm to 0.12 μm, a hard micro-protrusion array with moderate density and uniform height was constructed on the coating surface. This micro-protrusion array plays a supporting role in frictional contact, transforming sliding friction into point contact bearing, and uniformly dispersing shear stress, avoiding coating cracking or particle shedding due to stress concentration, thus achieving a balance between excellent scratch resistance and optical appearance.
[0021] (3) Through dual surface modification with silane coupling agent and 3,5-diaminobenzoic acid, combined with a multifunctional oxazoline crosslinking system, chemical anchoring and spatial stability of silica particles in the resin matrix were achieved. The steric hindrance provided by the rigid benzene rings overcomes the thermodynamic driving force of particle aggregation under high solid content, while the chemical crosslinking involving carboxyl groups permanently locks the particles onto the network nodes. This microstructure stability ensures the long-term consistency of the macroscopic surface morphology (Ra) during coating, drying, and subsequent use, eliminating the risk of surface defects caused by particle migration and aggregation. Attached Figure Description
[0022] Figure 1 This is a schematic diagram of the layered structure of the scratch-resistant polarizing plate of this application; Figure 2 A schematic diagram of the layered structure of a traditional polarizing plate.
[0023] Among them: 100, scratch-resistant polarizing plate; 110, compensation film; 120, first adhesive layer; 130, polarizer; 140, second adhesive layer; 150, acrylic resin film; 160, primer layer; 200, Traditional polarizing plate; 210, Compensation film; 220, First adhesive layer; 230, Polarizing element; 240, Second adhesive layer; 250, Acrylic resin film; 260, Primer layer. Detailed Implementation
[0024] To make the objectives, technical solutions, and advantages of this invention clearer, the specific embodiments of this invention are described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of this invention, not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0025] To verify the superior performance of the technical solution of this application, the following embodiments are also provided.
[0026] Example 1 like Figure 1 As shown, this embodiment provides a scratch-resistant polarizing plate 100, which includes, from top to bottom, a compensation film 110, a first adhesive layer 120, a polarizer 130, a second adhesive layer 140, an acrylic resin film 150, and a primer layer 160. The primer layer 160 is disposed on the side of the acrylic resin film 150 away from the polarizer 130, that is, the primer layer 160 is located on the outermost layer of the entire polarizing plate structure and directly serves as the interface for contact with the backlight module.
[0027] Primer layer 160 includes a resin crosslinking network and silica particles anchored in the resin crosslinking network. The resin crosslinking network is formed by crosslinking waterborne polyurethane with a multifunctional oxazoline polymer. The silica particles have active groups grafted onto their surfaces, and the silica particles are connected to the resin crosslinking network through the active groups as crosslinking nodes.
[0028] In this embodiment, the arithmetic mean roughness Ra of the primer layer 160 surface is 0.01 μm, and the solid content of silica particles in the primer layer 160 is 11%. This solid content refers to the percentage of the solid mass of silica particles to the total solid mass of the primer layer. This embodiment shows that the endpoint value of 11% also has excellent scratch resistance.
[0029] The preparation process of primer layer 160 is as follows. First, a modified silica particle sol is prepared. Step S101: 10 parts by weight of silica particles (secondary particle size 30 nm) are dispersed in a mixed solvent of ethanol and water. 2 parts by weight of γ-glycidoxypropyltrimethoxysilane are added, and the mixture is stirred at 60°C for 2 hours. This allows the silanol produced by the hydrolysis of the silane coupling agent to condense with the hydroxyl groups on the surface of the silica particles to form Si-O-Si covalent bonds, introducing epoxy groups onto the particle surface. Step S102: 2 parts by weight of 3,5-diaminobenzoic acid are added to the reaction system, and the mixture is reacted at 75°C for 3 hours. This allows the epoxy groups to undergo a ring-opening addition reaction with the amino groups to form bonds. Step S103: The reaction product is centrifuged and washed with water to remove impurities, and then redispersed in deionized water to prepare a modified silica particle sol with a solid content of 18%.
[0030] The coating solution is then prepared and applied. In step S201, 20 parts by weight of aqueous polyurethane emulsion (30% solid content) are diluted with 70 parts of water, then 4.84 parts of the aforementioned silica particle sol (18% solid content) and 4.2 parts of a multifunctional oxazoline polymer (25% solid content) are added. The mixture is stirred until homogeneous, filtered, and allowed to stand to remove bubbles, yielding the primer coating solution. The solid content of the silica particles in this formulation is 11%. In step S202, the acrylic resin film 150 is subjected to corona treatment on one side to improve adhesion, and then the aforementioned primer coating solution is applied to its surface. The film is then dried and cured at 80°C to form a primer layer 160 with a thickness of 280 nm.
[0031] Regarding other functional layers, the acrylic resin film 150 uses an acrylic resin film with a thickness of 40μm, which is made of polymethyl methacrylate resin, melt-extruded at 280°C by a twin-screw extruder to form a sheet with a thickness of 110μm, and then the sheet is stretched longitudinally by 2.0 times and transversely by 2.4 times at 160°C.
[0032] The compensation film 110 is a zero-phase-difference TAC film with a thickness of 40 μm.
[0033] Polarizer 130 uses a 30 μm thick polarizer, which is made by immersing a 75 μm thick polyvinyl alcohol (PVA) film in warm water at 28°C for 60 seconds to allow it to swell. It is then immersed in an iodine / potassium iodide aqueous solution (mass ratio 1:10) for staining, and simultaneously stretched to 3.3 times its original length. Next, it is immersed in a solution containing 3 wt% boric acid and 2 wt% potassium iodide for 10 seconds, and then stretched further at 60°C in a solution containing 4 wt% boric acid and 3 wt% potassium iodide, achieving a total stretch of 6.0 times. Finally, the film is immersed in a solution containing 5 wt% potassium iodide for 10 seconds and dried in an oven at 40°C for 3 minutes to obtain a 30 μm thick polarizer.
[0034] The first adhesive layer 120 and the second adhesive layer 140 contain an epoxy group resin prepolymer and a cationic photoinitiator, and both have a cured thickness of 3 μm. Both the first adhesive layer 120 and the second adhesive layer 140 can be prepared by the following method: 80 parts by weight of alicyclic epoxy resin (CELLOXIDE 2021P), 20 parts by weight of aromatic epoxy resin (EX-141), and 5 parts by weight of cationic photoinitiator (CPI-100P) are mixed in a weight ratio, stirred at room temperature until uniform and transparent, and then vacuum degassed and stored in a light-proof, sealed container.
[0035] The polarizing plate is assembled using a bonding process. A compensation film 110 and an acrylic resin film 150 with a primer layer 160 are bonded to both sides of the polarizer 130 via a first adhesive layer 120 and a second adhesive layer 140, ensuring that the primer layer 160 faces outwards, away from the polarizer 130. During bonding, the adhesive layers are cured by ultraviolet light. This embodiment achieves good scratch resistance and optical appearance under the lower limit condition of only 11% silica solids content.
[0036] Example 2 like Figure 1 As shown, the scratch-resistant polarizing plate 100 provided in this embodiment is consistent with the laminated structure of embodiment 1. From top to bottom, it includes a compensation film 110, a first adhesive layer 120, a polarizer 130, a second adhesive layer 140, an acrylic resin film 150, and a primer layer 160. The primer layer 160 is disposed on the side of the acrylic resin film 150 away from the polarizer 130.
[0037] In this embodiment, the preparation method of the modified silica particle sol is the same as in Example 1, except that the secondary particle size of the silica particles is 135 nm, the solid content is adjusted to 20%, the solid content of the silica particles in the primer layer 160 is 20%, and the arithmetic mean roughness Ra of the surface of the primer layer 160 is 0.06 μm. When preparing the coating solution, 20 parts by weight of aqueous polyurethane emulsion (30% solid content) are diluted with 70 parts of water, then 8.81 parts of modified silica particle sol with a solid content of 20% and 4.2 parts of polyfunctional oxazoline polymer (25% solid content) are added. After stirring evenly, filtering, and allowing to stand to remove bubbles, the primer coating solution is obtained.
[0038] The preparation process of the remaining functional layers is the same as that in Example 1, except that the thickness of the first adhesive layer 120 and the second adhesive layer 140 after curing is 1 μm, the thickness of the acrylic resin film 150 is 20 μm, and the thickness of the compensation film is 0.1 μm.
[0039] This embodiment selects a combination of 20% solid content and 135nm secondary particle size. Compared to the 30nm small particle size in Example 1, the 135nm silica particles have a larger single particle volume and rigidity, providing stronger single-point support when subjected to external friction loads and are less likely to be pressed into the resin matrix; the 20% solid content keeps the micro-protrusion density per unit area within a suitable range. Under this ratio, the micro-nano uneven structure formed on the coating surface is highly uniform, and the arithmetic mean roughness Ra is stably controlled at 0.06μm, enabling the polarizing plate to achieve a 3H pencil hardness and good scratch resistance.
[0040] Example 3 like Figure 1 As shown, the scratch-resistant polarizing plate 100 provided in this embodiment is consistent with the laminated structure of embodiment 1. From top to bottom, it includes a compensation film 110, a first adhesive layer 120, a polarizer 130, a second adhesive layer 140, an acrylic resin film 150, and a primer layer 160. The primer layer 160 is disposed on the side of the acrylic resin film 150 away from the polarizer 130.
[0041] In this embodiment, the preparation method of the modified silica particle sol is the same as in Example 1, except that the secondary particle size of the silica particles is 250 nm, the solid content is adjusted to 22%, the solid content of the silica particles in the primer layer 160 is 30%, and the arithmetic mean roughness Ra of the primer layer 160 surface is 0.12 μm. When preparing the coating solution, 20 parts by weight of aqueous polyurethane emulsion (30% solid content) are diluted with 70 parts of water, then 13.73 parts of modified silica particle sol with a solid content of 22% and 4.2 parts of polyfunctional oxazoline polymer (25% solid content) are added. After stirring evenly, filtering, and allowing to stand to remove bubbles, the primer coating solution is obtained.
[0042] The preparation process of the remaining functional layers is the same as that in Example 1, except that the thickness of the first adhesive layer 120 and the second adhesive layer 140 after curing is 5 μm, the thickness of the acrylic resin film 150 is 80 μm, and the thickness of the compensation film is 200 μm.
[0043] In this embodiment, the solid content of silica in the cured primer layer 160 reaches 30%, and the secondary particle size of the silica particles used is 250nm. With the combination of 30% solid content and 250nm particle size, a sufficient number of hard support points can be provided per unit area, while avoiding the risk of agglomeration caused by excessive specific surface area due to excessively small particle size. The polarizing plate can still maintain good optical appearance and mechanical strength.
[0044] Example 4 This embodiment provides a method for preparing a scratch-resistant polarizing plate, used to prepare the scratch-resistant polarizing plate described in any one of Embodiments 1 to 3 above. This embodiment focuses on process control during preparation, especially the control of the bonding direction and the selection of curing conditions.
[0045] The preparation method includes step S301, which provides an acrylic resin film with a primer layer on its surface. The primer layer can be formed by referring to the coating and drying process described in the previous embodiments, that is, coating one side of the acrylic resin film with a primer coating liquid containing modified silica particles and then curing it by heating.
[0046] In step S302, the compensation film and the acrylic resin film with a primer layer are bonded to both sides of the polarizer using the first adhesive layer and the second adhesive layer, with the primer layer facing outwards away from the polarizer. Directional control is crucial in the bonding process. On an automated bonding line, a vision recognition system or position sensor is needed to position the primer layer of the acrylic resin film, ensuring that when bonded to the polarizer, the clean side without primer faces the polarizer and is bonded through the second adhesive layer, while the side coated with the primer layer faces outwards.
[0047] In the step of bonding the compensation film and the acrylic resin film with the primer layer to both sides of the polarizer, the first and second adhesive layers are cured by ultraviolet irradiation. This curing method can induce a strong acid generated by the cationic photoinitiator, which catalyzes the ring-opening polymerization reaction of the epoxy group resin prepolymer to form a three-dimensional cross-linked network. This curing process ensures that the adhesive layer is fully cured within a thickness range of 1μm to 5μm, while avoiding the risk of thermal deformation or yellowing of the optical film material due to excessive temperature or excessive irradiation.
[0048] To verify the synergistic effect of the core technical features in this application and the critical significance of their parameter ranges, the following five sets of comparative examples were set up. All comparative examples used Example 2 as the baseline sample with a single variable substitution. Except for the specific changes described below, the other components, preparation processes, and test conditions of each comparative example were consistent with Example 2.
[0049] Comparative Example 1 The only difference between this comparative example and Example 2 is the layered structure of the polarizer. In this comparative example, the primer layer is disposed between the acrylic resin film and the second adhesive layer (i.e., on the inner side), with the acrylic resin film located on the outermost side and directly contacting the backlight module. This structure replicates the design of a conventional polarizer and is used to verify the effect of the primer layer position on scratch resistance.
[0050] Comparative Example 2 The only difference between this comparative example and Example 2 is that the solid content of silica particles in the primer coating solution is 6%. This value is lower than the 11% lower limit specified in this application, and is used to verify whether an effective protective micro-protrusion can be formed on the coating surface when the content of hard particles is insufficient.
[0051] Comparative Example 3 The only difference between this comparative example and Example 2 is that the solid content of silica particles in the primer coating solution is 38%. This value is higher than the 30% upper limit specified in this application, and is used to observe the changes in the surface morphology and mechanical properties of the coating when the particle content is too high and exceeds the steric hindrance shielding limit.
[0052] Comparative Example 4 The only difference between this comparative example and Example 2 is the preparation method of the silica particle sol. This comparative example omits the steps of adding γ-glycidoxypropyltrimethoxysilane and 3,5-diaminobenzoic acid, directly dispersing unmodified silica particles in deionized water to prepare the sol. This comparative example is used to verify the difference between physical mixing and chemical anchoring in maintaining the stability of high-solids-content systems.
[0053] Comparative Example 5 The only difference between this comparative example and Example 2 is that the addition of 3,5-diaminobenzoic acid was omitted during the preparation of the silica particle sol. That is, the silica particles were only treated with a silane coupling agent to introduce epoxy groups, but no rigid groups containing benzene rings or carboxyl groups were grafted onto them. This comparative example is used to verify the role of the steric hindrance effect provided by 3,5-diaminobenzoic acid in inhibiting particle aggregation and preventing migration.
[0054] The manufacturers and product models of the various drugs and raw materials involved in the above embodiments and comparative examples are as follows: Waterborne polyurethane can be selected from commercially available products, such as Daiichi Kogyo Pharmaceutical's SUPERFLEX series SUPERFLEX 300, SUPERFLEX 500M, SUPERFLEX 210, etc. Multifunctional oxazoline polymers can be selected from commercially available products, such as Nippon Shokubai's EPOCROS series WS-300, WS-500, WS-700, K-2010E, K-2020E, K-2035E, etc. The compensation membrane used is the "Zero-Tac" product manufactured by Konica Minolta Opto. The epoxy group resin prepolymer is selected from at least one of alicyclic epoxy resin (CELLOXIDE 2021P) and aromatic epoxy resin (EX-141); The cationic photoinitiator is selected from cationic photoinitiator CPI-100P.
[0055] The polarizing plates prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were tested for pencil hardness, scratch resistance, and arithmetic mean roughness Ra. The test standards for each property are as follows: I. Pencil Hardness: Pencil hardness is graded into 13 levels, from hardest to softest: 6H, 5H-H, HB, B, 2B-6B. The specific testing methods are as follows: Step S1: Use a pencil hardness tester to test the hardness of the products from each embodiment and comparative example, cutting them into pieces of 5cm size. A 15cm test piece was fixed on the testing machine with the primer side (comparative example 1 uses the acrylic resin film side) facing upwards. Pencils of varying hardness were used, held at a 45° angle to the test piece, to draw a 10mm mark forward at a speed of 5mm / s. After each mark, the tip of the pencil lead was ground, and this process was repeated 5 times.
[0056] Step S2: Observe the five marks on the test piece. If two or more marks cause damage to the primer layer or acrylic resin film layer, the test piece is deemed to fail the hardness grade. If one or fewer marks are damaged, the test piece is deemed to pass the hardness grade.
[0057] II. Scratch resistance: The primer surface of each polarizing plate (comparative example 1 is the acrylic resin film surface) was rubbed 1000 times under a load of 500 g / cm² using a reciprocating abrasion tester. The degree of damage was visually assessed under three-color light sources. ◎: No scars; ○: Several small scratches appeared; ×: The entire surface is scratched.
[0058] III. Arithmetic mean roughness Ra: The arithmetic mean roughness Ra was measured using a white interferometer "Vertscan" manufactured by Ryuka Systems Co., Ltd. as a non-contact surface roughness measuring instrument, in accordance with JIS B 0601:2013 standard.
[0059] Measurement principle: The instrument uses a CCD camera to capture the interference fringes caused by the optical path difference generated by the unevenness of the sample surface, and converts the brightness and darkness information of the interference fringes into the height information of the unevenness of the surface.
[0060] Equipment parameter settings: Magnification of the double-beam interference objective: 5x Measurement mode: Select "wave" Wavelength filter: Select "530white" Scan range (z-direction): -10μm to 10μm Stitching settings: 2×2, overlap rate 20%.
[0061] Based on the above settings, the observation range is as follows.
[0062] Vertical (x) × Horizontal (y): 1263.73 μm × 1689.94 μm Elevation difference (z): -0.25μm to 0.25μm.
[0063] Measurement Procedure: First, cut 20cm × 20cm test pieces from each polarizing plate. Place each test piece with the primer side (TA side of the acrylic resin film in Comparative Example 1) facing upwards on a black acrylic plate, and secure it around the edges with tape to flatten the surface to be measured. Use the resulting laminate as the measurement sample. Place the measurement sample on the stage of a white interferometer "Vertscan" and perform the measurement using the following setup to obtain the arithmetic mean roughness Ra.
[0064] The test results are shown in Table 1: Table 1
[0065] Note: In the scratch resistance evaluation standard, "◎" indicates no scratches; "○" indicates a few small scratches; and "×" indicates scratches on the entire surface.
[0066] Based on the data in the table above, the failure mechanisms of each comparative example are analyzed as follows: A comparison of Example 2 and Comparative Example 1 shows that both have the same composition and solid content in their primer layers. However, Comparative Example 1 uses a traditional built-in structure, resulting in the low-hardness acrylic resin film being directly exposed to the friction interface. Test results show that the surface roughness Ra of Comparative Example 1 is only 0.002 μm (this is the roughness of the acrylic resin itself), the pencil hardness drops to H level, and the scratch resistance evaluation is "×" (scratched across the entire surface). In other words, a hard coating material alone, without an external structure, cannot solve the problem of easy scratching of the backlight-side protective film. Placing the primer layer on the outermost layer in this application is a prerequisite for achieving scratch resistance.
[0067] A comparison of Example 2 with Comparative Examples 2 and 3 shows that the solid content of silica needs to be controlled within the range of 11% to 30%. In Comparative Example 2, the solid content was 6%, lower than the lower limit of 11%. A low solid content results in particles being completely coated by the resin matrix, lacking sufficient hard support points on the surface, with an Ra value as low as 0.007 μm, failing to effectively resist mechanical loads and causing scratch resistance failure. In Comparative Example 3, the solid content was 38%, exceeding the upper limit of 30%. Even with modified groups, the excessively high particle density would exceed the steric hindrance shielding limit, leading to severe agglomeration and stacking. This caused the Ra value in Comparative Example 3 to rise to 0.24 μm. The resulting macroscopic protrusions became stress concentration points during friction, easily detaching and scratching the contact surface, thus reducing scratch resistance. This demonstrates the importance of limiting the range of silica solid content in this application.
[0068] A comparison of Example 2 and Comparative Example 4 shows that simple physical mixing cannot meet the dispersion requirements under high solid content. Similar to Example 2, Comparative Example 4 also had a solid content of 20%, but due to the lack of chemical modification and cross-linking anchoring, the silica particles severely agglomerated during the coating and drying process and did not participate in the cross-linking reaction of the resin network. Its Ra value was 0.19 μm, indicating the formation of disordered protrusions of varying heights on the surface; its pencil hardness was only H, indicating weak adhesion between the particles and the matrix, making it easily peeled off under stress. In other words, this application, through the dual modification of silane coupling and 3,5-diaminobenzoic acid, and the mechanism of anchoring particles as cross-linking nodes in the network, ultimately achieves a coating with excellent uniformity and durability.
[0069] A comparison of Example 2 and Comparative Example 5 shows that the steric hindrance effect provided by 3,5-diaminobenzoic acid is indispensable. Although Comparative Example 5 achieved the grafting of the silane coupling agent, the lack of rigid benzene ring groups resulted in insufficient steric barriers between particles to overcome van der Waals forces and hydrogen bonding. At high solid content, significant migration and soft aggregation of particles still occurred, causing the Ra value to rise to 0.15 μm, exceeding the range of 0.01 μm to 0.12 μm in this application. Simultaneously, due to the lack of carboxyl groups participating in crosslinking, the particles were not firmly fixed in the network, and the scratch resistance evaluation dropped to "○". This indicates that chemical bonding alone, without steric hindrance stability, is insufficient to achieve precise morphology control and protective performance.
[0070] In summary, through the verification of Examples 1 to 5, it can be seen that the external structure, the specific solid content range, and the dual-modified cross-linking anchoring mechanism all play an indispensable role in the technical solution of this application. The absence or deviation of any of these features will lead to the deterioration or even failure of scratch resistance.
[0071] The embodiments of the present invention have been described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and these variations still fall within the protection scope of the present invention.
Claims
1. A scratch-resistant polarizing plate, characterized in that, From top to bottom, it includes a compensation film, a first adhesive layer, a polarizer, a second adhesive layer, an acrylic resin film, and a primer layer; wherein: The primer layer is disposed on the side of the acrylic resin film away from the polarizer; The primer layer comprises a resin crosslinking network and silica particles anchored in the resin crosslinking network; The arithmetic mean roughness Ra of the primer layer surface is 0.01 μm to 0.12 μm; The solid content of silica particles in the primer layer is 11% to 30%, and the solid content percentage is the percentage of the solid mass of the silica particles to the total solid mass of the primer layer.
2. The scratch-resistant polarizing plate according to claim 1, characterized in that, The thickness of the primer layer is 120 nm to 400 nm; The resin crosslinking network is formed by crosslinking waterborne polyurethane with a multifunctional oxazoline polymer. The surface of the silica particles is grafted with active groups, and the silica particles are connected to the resin crosslinking network through the active groups as crosslinking nodes. The secondary particle size of the silica particles is 30nm to 250nm.
3. The scratch-resistant polarizing plate according to claim 2, characterized in that, The surface of the silica particles is grafted with rigid groups that provide steric hindrance and carboxyl groups that serve as the active groups. The hydroxyl groups on the surface of the silica particles are connected to silane coupling agent residues via Si-O-Si bonds. The epoxy groups of the silane coupling agent residues react with the amino groups of 3,5-diaminobenzoic acid to form bonds, thereby introducing the rigid group and the carboxyl group. The rigid group is a benzene ring-containing group.
4. The scratch-resistant polarizing plate according to claim 3, characterized in that, The primer layer is formed by coating a primer coating solution and drying it. The preparation method of the primer coating solution includes: diluting an aqueous polyurethane emulsion with water, adding silica particle sol and the multifunctional oxazoline polymer, stirring evenly, filtering and allowing it to stand to remove bubbles, and obtaining the primer coating solution.
5. The scratch-resistant polarizing plate according to claim 1, characterized in that, The acrylic resin film is made from polymethyl methacrylate resin through melting, extrusion, and stretching; The acrylic resin film has a thickness of 20μm to 80μm and a total light transmittance of 92% to 98%.
6. The scratch-resistant polarizing plate according to claim 1, characterized in that, The first adhesive layer and the second adhesive layer comprise an epoxy group resin prepolymer and a cationic photoinitiator; The thickness of both the first adhesive layer and the second adhesive layer after curing is 1μm to 5μm.
7. The scratch-resistant polarizing plate according to claim 1, characterized in that, The compensation membrane comprises at least one of cyclic olefin polymers, cellulose triacetate, polyester resins, polycarbonate resins, polyimide resins, acrylic resins, or polystyrene resins. The thickness of the compensation membrane is 0.1 μm to 200 μm.
8. The scratch-resistant polarizing plate according to claim 1, characterized in that, The polarizers are prepared from polyvinyl alcohol film through processes of swelling, dyeing, stretching, washing and drying.
9. A method for preparing a scratch-resistant polarizing plate as described in any one of claims 1 to 8, characterized in that, include: Provide an acrylic resin film with a primer layer on its surface; The compensation film and the acrylic resin film with a primer layer are respectively bonded to both sides of the polarizer through the first adhesive layer and the second adhesive layer, with the primer layer facing away from the polarizer.
10. The method for preparing a scratch-resistant polarizing plate according to claim 9, characterized in that, In the step of bonding the compensation film and the acrylic resin film with the primer layer to both sides of the polarizer, the first adhesive layer and the second adhesive layer are cured by ultraviolet irradiation.
